An antibody attack against body wasting in cancer - Rohm, Maria; Herzig, Stephan (Cell metabolism, 2020)
Cachexia is a devastating, non-curable condition in many cancer patients that is marked by severe wasting of the muscle and fat tissue. Its prevention has been hampered by an insufficient knowledge of the underlying molecular mechanism(s) that lead to its pathogenesis. Suriben et al. (2020) now report the development and characterization of an antagonistic antibody for the previously identified GDF15-GFRAL axis that efficiently blocks tumor-induced body wasting in experimental animals.
Gesehen am 27.11.2020